Giribawa, Sri Lanka. An exceptional site of raw glass and glass bead production. Season 2022 - de Saxcé, Ariane (e-Forschungsberichte des DAI, 2023)
A new excavation has started in February 2022 on the site of Giribawa, in the north-west of Sri Lanka. Its occupation goes back to the early medieval period and probably earlier. The remains that could be identified include bead-making furnaces, glass waste, finished beads, and raw glass fragments, indicating raw glass production on the same site. The chemical composition of the beads and the raw glass are similar. Further investigations on the site will focus on the cultural sequence, the chronology, the location of a settlement area and the technological details of this very specific type of semi-circular furnaces.